Risk transfer for multilateral development banks: Obstacles and potential - Federico Galizia; William R. M. Perraudin; Andrew Powell; Timothy Turner (Inter-American Development Bank (IDB), 2021)
Long-term development finance provided by Multilateral Development Banks (MDBs) is key to advancing the United Nations 2015 Sustainable Development Goals. However, MDBs are constrained in their lending by the availability of capital. This paper argues that Risk Transfer, as a complement to equity injections, could permit higher MDB lending by attracting a broader class of investors. We describe selected examples of actual Risk Transfer transactions and provide estimates of the potential expansion in lending these techniques could yield. But we also identify obstacles that limit investors willingness and ability to participate in these transactions. Therefore, we recommend an agenda for international policymakers to open the way for the wider use of Risk Transfer. Still, we recognize this will be a gradual process which cannot substitute for MDB expansion through additional ordinary capital resources.
Keywords: F53; O16; G15; 330; Risk Transfer; International Financial Architecture; G20; Multilateral Development Banks; Securitization; Rating Agencies; Preferred Creditor Treatment; Development